Sustainable consumption – examining the environmental and health awareness of students at the University of Debrecen - Andrea Bauerné Gáthy; Angéla Kovácsné Soltész; István Szűcs (Cogent Business & Management, 2022)
Environmental awareness and health awareness, as part of a sustainable conscious food consumer philosophy, differ in form and extent among societies and countries. The main purpose of this paper was to identify the relationship between the target group's (university students) self-perceived and actual health and environmental awareness, based on their actual consumer behaviour. A questionnaire survey (n~=~500) was conducted among the students of the University of Debrecen (UD), Hungary. Several multivariate statistical techniques were applied for the data analysis: principal component analysis, cross-tabulation analysis, exploratory and confirmatory factor analysis, multivariate data reduction techniques and cluster analysis. Following four factors were identified: Organic Food Preference, Price Consciousness, Quality Aspects, Food Information. As a result of the cluster analysis four clusters were formed ("Price-oriented Food Consumers", "Fashionable Organic Food Consumers", "Habitual Food Consumers", "Conscious Food Consumers"). Only the fourth cluster members can be characterised by health and environmental awareness, most of them study health and economics. The obtained findings led to the conclusion that health and environmentally conscious food consumption is at a fairly low level among UD students, i.e. improvement is definitely desirable and higher education can play a significant role in this field.
Keywords: 650; eco-conscious; education for sustainable development; health conscious; sustainable food consumption; university students